Comparative Effectiveness of the Corticosteroid Injection and Prolotherapy in Patients With Hallux Rigidus: A Clinical Trial - Mohammadjavad Hadianfard; Batoul Safari; Leila Sadat Mohamadi Jahromi (Iranian Rehabilitation Journal, 2023)
Objectives: Hallux rigidus is one of the main etiologies of disability in the elderly. It is a degenerative disease of the first metatarsophalangeal joint causing restriction of movement as well as pain and swelling. This study was conducted to evaluate the effectiveness of methylprednisolone and dextrose prolotherapy in pain reduction and functional improvement of patients with hallux rigidus. Methods: A randomized double-blind control trial was designed with the inclusion of 32 patients assigned to the two groups. Group one received a mixture of 1 cc methylprednisolone 40 mg with 1 cc lidocaine 2% while the second group received a combination of 1 cc dextrose 50% with 1 cc lidocaine 2%. Standard questionnaires, including visual analog scale (VAS) and Manchester-Oxford foot questionnaire (MOXFQ) were completed by all patients at baseline and 1, 4, and 8 weeks after injections. Results: Both groups revealed significant improvement in VAS and MOXFQ scores 1, 4, and 8 weeks post-injection with no difference between the two groups in the follow-up. Discussion: Both corticosteroid injections and prolotherapy are effective in pain reduction and functional improvement in patients with hallux rigidus but neither is superior to the other.